DINAMIKA PENERAPAN KURIKULUM KMI DALAM SISTEM PENDIDIKAN PESANTREN MODERN - Syafri Royyan Abdillah; Akhmad Syahri; Musta’in (Walada: Journal of Primary Education, 2026)
Nurul Haramain NWDI Narmada Modern Islamic Boarding School is one of the Islamic educational institutions that adopts the KMI curriculum in its educational system. This Islamic boarding school has its own characteristics in integrating the core curriculum with the modern Islamic boarding school education system that emphasizes character building, discipline, and foreign language proficiency. The implementation of the KMI curriculum in this institution is certainly inseparable from various dynamics, both in the aspects of planning, implementation, and evaluation of learning. The objectives of this study are to: (1) describe the implementation of the KMI curriculum in the modern Islamic boarding school education system; (2) analyze the dynamics that occur in the implementation process; and (3) identify supporting and inhibiting factors in the implementation of the KMI curriculum at Nurul Haramain NWDI Narmada Modern Islamic Boarding School. This study uses a qualitative approach with a narrative inquiry type. The results of the study show (1) the KMI curriculum is implemented comprehensively in shaping the academic competencies, skills, and character of students. (2) In the implementation process, various dynamics emerge which indicate that the implementation of the KMI curriculum is not static, but continues to develop and adapt. (3) There are supporting and inhibiting factors in implementing this KMI curriculum. Through this research, we can see that the KMI curriculum can have a positive impact on students and teachers in achieving educational goals.